A 3-year retrospective review of mortality in women of reproductive age in a tertiary health facility in Port Harcourt, Nigeria - Orazulike NC; Alegbeleye JO; Obiorah CC; Nyengidiki TK; Uzoigwe SA (Dove Medical Press, 2017)
Ngozi C Orazulike,1 Justina O Alegbeleye,1 Christopher C Obiorah,2 Tamunomie K Nyengidiki,1 Samuel A Uzoigwe1 1Department of Obstetrics and Gynecology, 2Department of Anatomical Pathology, University of Port Harcourt Teaching Hospital, Port Harcourt, Rivers State, Nigeria Purpose: To determine the causes of death and associated risk factors among women of reproductive age (WRA) in a tertiary institution in Port Harcourt, Nigeria.Patients and methods: This was a retrospective survey of all deaths in women aged 15–49 years at the University of Port Harcourt Teaching Hospital that occurred from January 1, 2013 to December 31, 2015. Data retrieved from ward registers, death registers, and death certificates were analyzed with Epi Info version 7. Comparison of socioeconomic and demographic risk factors for maternal and nonmaternal deaths was done using a multivariate logistic regression model.Results: There were 340 deaths in the WRA group over the 3-year period. The majority (155 [45.6%]) of the women were aged 30–39 years. There were 265 (77.9%) nonmaternal deaths and 75 (22.1%) maternal deaths. Among the nonmaternal deaths, 124 (46.8%) had infectious diseases, with human immunodeficiency virus being the most common cause of infection in this group. Breast cancer (13 [4.9%]), cervical cancer (12 [4.5%]), and ovarian cancer (11 [4.2%]) were the most common malignant neoplasms observed. Hypertensive disorders of pregnancy (31 [41.3%]) and puerperal sepsis (20 [26.7%]) were the most common causes of maternal deaths. Age and occupation were significantly associated with deaths in WRA (p<0.05). Older women aged >30 years (odd ratio =1.86, 95% CI =1.07–3.23) and employed women (odds ratio =2.55, 95% CI =1.46–4.45) were more likely to die from nonmaternal than maternal causes.Conclusion: Most of the deaths were nonmaternal. Infectious diseases, diseases of the circulatory system, and malignant neoplasms were the major causes of death among WRA, with maternal deaths accounting for approximately a quarter. Public health programs educating women on safer sex practices, early screening for cancers, benefits of antenatal care, and skilled attendants at delivery will go a long way to reducing preventable causes of deaths among these women. Keywords: maternal deaths, nonmaternal deaths, causes of death, infectious diseases